Fuzzy Datalog with background knowledge - Achs, Ágnes (Teaching Mathematics and Computer Science, 2005)
In this paper we give a possible model for handling uncertain information. The concept of fuzzy knowledge-base will be defined as a triplet of a background knowledge defined by the similarity of predicates and terms; a deduction mechanism: a fuzzy Datalog program, and a decoding set of the program, which help us to determine the uncertainty level of the results.